Geoscience of Climate and Energy 13. The Environmental Hydro-geology of the Oil Sands, Lower Athabasca Area, Alberta - Miall, Andrew (Geoscience Canada, 2013)
SUMMARY Shallow fresh groundwater and deep saline groundwater are used together with surface water in the extraction of bitumen from the Athabasca Oil Sands both in the surface mining and in situ operations. However, increasing efficiencies in processing technologies have reduced water use substantially and currently at least 75% of the water used in most operations is recycled water. Much concern has been expressed regarding contamination of surface waters by seepage from tailings ponds, but hydrogeological studies indicate that this is not happening; that seepage capture design is effective. Oil sands mining and in situ project licensing and operation regulations include Environmental Impact Assessments that mandate considerable hydrogeo-logical measurement and monitoring work. However, little of this is independently evaluated for accuracy or synthesized and interpreted for the public. Recent changes in Alberta environmental regulation, including the establishment of the Alberta Environmental Monitoring Management Board (in October 2012) are expected to bring new transparency to environmental management of Oil Sands operations.